Surgical resection for small cell carcinoma of the lung: a retrospective study. Issue 1 (January 1994) - Smit, E F; Groen, H J; Timens, W; de Boer, W J; Postmus, P E
Abstract : BACKGROUND--A retrospective review was undertaken of the survival of 21 patients with histologically proven small cell carcinoma of the lung resected between 1977 and 1991. METHODS--Twenty one patients (20 men) of median age 60 (range 44-73) years underwent surgical resection. Patients were subjected to standard clinical staging procedures. Preoperative diagnosis was small cell carcinoma of the lung in 13, non-small cell lung cancer in one, and uncertain in seven patients. Clinical staging was stage I disease in 11 and stage II in 10 patients. RESULTS--Resection included pneumonectomy in 12 cases, lobectomy in eight, and one wedge resection. Resection was complete in 16 patients. Postoperative histopathological examination confirmed small cell carcinoma of the lung in 19 specimens and mixed small cell and non-small cell carcinoma of the lung in two. Pathological staging was stage I in 11, stage II in three, and stage III in seven patients. The final pathological diagnosis of the resected specimens (n = 18) was atypical carcinoid in one, pure small cell carcinoma of the lung in 15, and mixed small cell and non-small cell carcinoma of the lung in two patients. Fourteen patients also received chemotherapy and 10 received prophylactic cranial irradiation postoperatively. Excluding the patient with a final diagnosis of atypical carcinoid, the median survival (n = 20) was 29 months (range two to 133+). Median survival for patients with pathological stage I and II disease (n = 13) was 40 months (range nine to 133+) and for patients with pathological stage III disease (n = 7) 20 months (range two to 116+). The median disease free survival was 23 months. Eleven patients relapsed between two and 101 months. There was no advantage for those patients who received postoperative chemotherapy. CONCLUSION--Curative resection offers the best chance for long term survival in patients with small cell carcinoma of the lung with very limited stage disease.